Implementation of Playdate with OBO Event Program to Increase Service Satisfaction at OBO Studio n' Play - Mutiara, Ken Reyhan (GENIUS: Indonesian Journal of Early Childhood Education, 2021)
Abstract Careful program planning to provide services for children's learning and play activities is an important thing to note. Because it will greatly affect the social, cognitive, sensory, and motor growth of children. With the aim of increasing revenue and demand as well as maximum service satisfaction, planning programs event marketing can be carried out by companies. Using qualitative research methods and data collection by distributing questionnaires based on the dimensions of service quality, namely Tangible, Empathy, Reliability, Responsiveness, and Assurance (TERRA). The results of the questionnaire were obtained from the parents of children who participated in the Playdate With OBO event produce outputs in the form of Terms of Reference containing programs regarding children's activities and stages of implementation. The activities of pre-school children contained in the Terms of Reference based on the advice of child psychologists and program planners for pre-school age children. Keywords: event marketing, kids preschool activity, preschool program, service quality